2011
DOI: 10.1242/jcs.086280
|View full text |Cite
|
Sign up to set email alerts
|

Rac deletion in osteoclasts causes severe osteopetrosis

Abstract: SummaryCdc42 mediates bone resorption principally by stimulating osteoclastogenesis. Whether its sister GTPase, Rac, meaningfully impacts upon the osteoclast and, if so, by what means, is unclear. We find that whereas deletion of Rac1 or Rac2 alone has no effect, variable reduction of Rac1 in osteoclastic cells of Rac2 2/2 mice causes severe osteopetrosis. Osteoclasts lacking Rac1 and Rac2 in combination (Rac double-knockout, RacDKO), fail to effectively resorb bone. By contrast, osteoclasts are abundant in Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 33 publications
9
106
0
Order By: Relevance
“…13 Although the results are somehow conflicting and their precise function not elucidated yet, both Rac1 and Rac2 seem to be important for the formation of the podosome belt and for bone resorption. 31,[63][64][65][66] This confirms earlier studies showing podosome belt disruption in osteoclasts where Rac1 and Rac2 have been neutralized by specific antibodies. 67 Using DNA microarray, we analyzed the expression profile of 76 GEFs of the Dbl and Dock families in osteoclasts.…”
Section: Adhesion Structuressupporting
confidence: 88%
See 2 more Smart Citations
“…13 Although the results are somehow conflicting and their precise function not elucidated yet, both Rac1 and Rac2 seem to be important for the formation of the podosome belt and for bone resorption. 31,[63][64][65][66] This confirms earlier studies showing podosome belt disruption in osteoclasts where Rac1 and Rac2 have been neutralized by specific antibodies. 67 Using DNA microarray, we analyzed the expression profile of 76 GEFs of the Dbl and Dock families in osteoclasts.…”
Section: Adhesion Structuressupporting
confidence: 88%
“…Although the authors agree on the increase in bone density, there are discrepancies regarding the mechanisms involved that will need further investigation. 31,[63][64][65] Interestingly, the absence of a single Rac GEF, such as Vav3, Dock5 or FARP2, is sufficient to result in osteoclasts impaired resorption in vivo, through distinct mechanisms. [68][69][70] The higher bone density observed in mice deficient for Rho GTPase signaling highlights them as targets in diseases with increased bone resorption such as post-menopausal osteoporosis or cancer-associated osteolysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We show here that tensin 3 can potentiate Dock5 exchange activity towards Rac. We also found that tensin 3 is necessary for the correct patterning of osteoclast podosomes, which is known to also require Dock5 (Vives et al, 2011), Rac (Razzouk et al, 1999;Wang et al, 2008;Croke et al, 2011) and the activation of Rac by Dock5 (Vives et al, 2015).…”
Section: Manzanaresmentioning
confidence: 55%
“…Cdc42, another Rho GTPase, exerts only a mild cytoskeletal effect through atypical PKCs, and its major impact is on proliferation of osteoclast precursors and survival of mature osteoclasts (170). In contrast, Rac1 and Rac2 function as two key effector molecules of the αvβ3 integrin, as their deletion results in a severe compromise of the osteoclast cytoskeleton and osteopetrosis (171). Integrin αvβ3 mediated cytoskeleton organization leads to the formation of the actin ring, which isolates the resorptive space from its surroundings (Figure 4).…”
Section: Establishment Of the Resorption Compartmentmentioning
confidence: 99%